A TAXONOMY OF THE TYPES OF PUBLIC SPORTING EVENTS - Beatrice ABĂLAȘEI (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2011)
The study has an exploratory character and its objective is to analyze the types of audience from sporting events throughexpertise in sports, using categorial content / thematic analysis. The results will identify features of violence in sports,focusing on the behaviour of fans. A typology of sports audience will emphasize these results on a systematic basis ofbehaviour, reactions, knowledge level concepts of sports, purpose.The study findings lead us toward the idea that the social actors in the lot, or the public, are influenced and led by aleader, an idea that spreads fast and come in all homes, leading to exaggerated reactions to messages received, so thatleads to collective behaviors. Even if these crowds are artificial or natural, non-homogenous or homogenous, active orpassive or aggressive here and calm in their vastness, the unconscious is the topping reality at a time of crisis decisionmakingand guidance distructive energies.